Stabilisation thermique des infrastructures routières construites sur pergélisol sensible au dégel à l'aide de surface à albédo élevé - Richard, Caroline (Université Laval, 2018)
The construction of transport infrastructure in northern environments inevitably affects the thermal balance of permafrost. First, the geometry of the embankment leads to changes of the drainage pattern and the snow cover extents. Furthermore, excavation or addition of materials modifies the thermal properties and the capacity of the surface to absorb or to reflect solar radiation. Also, impacts of global warming, such as rising average air temperatures and changes in the frequency and intensity of precipitation, have a direct impact on the stability of permafrost and, thus, on the structural capacities of infrastructure. The design of pavement built on permafrost must be adapted to maintain safety and functionality for the expected lifetime of the road. One of the proposed solutions is the application of high albedo coatings to limit heat absorbed by solar radiation underneath the embankment. As part of the project, road sections were constructed using high albedo surfaces and instrumented to evaluate the thermal performance. Numerical modelling using GeoStudio’s TEMP/W software was developed to accomplish the twofold research objectives: to propose a thermal stabilization method based on the albedo of the surface, and to simulate the effect of embankment height on the thermal regime of the soil. Simulations allow the modelling of heat exchange in a soil column, and, through analyzing the results, an equivalent surface albedo that can stabilize the natural soil can be calculated. The stabilization approach is based on a required temperature gradient, which is the difference between the interface temperature and the permafrost temperature. A zero or negative temperature gradient indicates that heat induced underneath the embankment is equal to or lower than heat extracted. Therefore, temperature of the natural soil remains constant or decreases. A validation of the model is presented for the Beaver Creek study site.--Résumé de l'éditeur. La construction d’infrastructures en milieu nordique affecte ...